Multiple Idiopathic Apical Root Resorption: a Case Report - L. Khojastepour; P. Bronoosh; M. Azar (Tehran University of Medical Sciences, 2010)
The aim of this case report was to present a case of multiple idiopathic apical root resorption which is a rare condition in a 17-year-old adult male. External root resorption of the permanent teeth is a multifactorial process. Well-recognized causes of apical root resorption in permanent teeth include orthodontic therapy, trauma, periapical or periodontal inflammation, tumors, cysts, occlusal stress, impacted teeth, systemic conditions, endocrine imbalances and dietary habits. When none of these causes are present, it is termed idiopathic root resorption which may be either cervical or apical. Multiple idiopathic apical root resorption is a rare condition which is usually detected as an incidental radiographic finding. However, it may cause pain and mobility in severe cases.